2012
DOI: 10.1097/bot.0b013e31821d6f55
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Surgical Treatment of Periprosthetic Femur Fractures Can Reduce Mortality: Comparison of Open Reduction and Internal Fixation versus a Modular Prosthesis Nail

Abstract: Treatment of periprosthetic femur fractures with femoral component exchange to a modular prosthetic nail that allows immediate postoperative full weightbearing may decrease mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 27 publications
2
10
0
1
Order By: Relevance
“…These authors observed a higher 1-year mortality rate in patients treated with internal fixation (33%) than those treated with revision arthroplasty (12%) in type B fractures. Moreover, immediate postoperative full weight bearing has been related to lower total and 6-month mortality in a recent article [28]. Another study confirmed that a delay to surgery of greater than 2 days from admission increased the 1-year mortality rate [26].…”
Section: Discussionmentioning
confidence: 87%
“…These authors observed a higher 1-year mortality rate in patients treated with internal fixation (33%) than those treated with revision arthroplasty (12%) in type B fractures. Moreover, immediate postoperative full weight bearing has been related to lower total and 6-month mortality in a recent article [28]. Another study confirmed that a delay to surgery of greater than 2 days from admission increased the 1-year mortality rate [26].…”
Section: Discussionmentioning
confidence: 87%
“…[4][5][6] The earlier weight bearing and improved mobilization associated with revision arthroplasty with implants that span the fracture may provide for improved mortality rates if patients who can withstand the magnitude of such surgery are properly selected. However, revision of an associated well-fixed stem to a long-stem modular prosthesis nail that spans the fracture has recently been advocated by several authors for Vancouver B fractures regardless of the stem stability.…”
Section: Revision Hip Arthroplastymentioning
confidence: 99%
“…49 Furthermore, this study demonstrated an 8-fold higher mortality rate (7.3%) seen in the patients with periprosthetic fracture. Langenhan et al, 5 because of high mortality rates after ORIF, altered their treatment protocol in 2001 and began performing stem replacement with a distally locked modular prosthesis nail for the majority of periprosthetic femur fractures, Vancouver B and C, regardless of the stem stability. Langenhan et al, 5 because of high mortality rates after ORIF, altered their treatment protocol in 2001 and began performing stem replacement with a distally locked modular prosthesis nail for the majority of periprosthetic femur fractures, Vancouver B and C, regardless of the stem stability.…”
Section: Revision Hip Arthroplastymentioning
confidence: 99%
“…The postoperative period is also challenging for patients, given the burden of medical co-morbidities in this population, as well as the frequent need for extended periods of protected weightbearing [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%